Малые олимпийские игры в сельской школе: из опыта работы / В. Г. Гришин, И. Г. Гришин - Гришин Владимир Григорьевич (Просвещение, 1989)
Экземпляры: КХ (20110331) / Инвентарный номер: 0285490 / Цена: 0.15 / Сис.шифр: 74.200.54 / Авт.знак: Г 85 / ГРНТИ: 14 / ББК: 74.200.554